Mixed Anionic and Cationic Redox Chemistry in a Tetrathiomolybdate Amorphous Coordination Framework. (28th July 2020) - Zhu, Qi; Wang, Jiande; Liu, Xuelian; Ebejer, Neil; Rambabu, Darsi; Vlad, Alexandru
Abstract: We report the electrochemistry of a hitherto unexplored Na2 MoS4 phase as a conversion electrode material for Na‐ and Li‐ion batteries. The material adopts an amorphous coordination polymer structure with mixed Mo and S valences. XPS and XRD analysis reveal a complex interplay between Mo and S redox chemistry, while excluding the formation of free sulfur, lithium sulfide, or other crystalline phases. Na2 MoS4 behaves as a mixed ionic–electronic conductor, with electronic conductivity of 6.1×10 −4 S cm −1, that permits carbon‐free application in an electrochemical cell. A reversible capacity of up to 500 mAh g −1 was attained, corresponding to a five‐electron redox exchange, with species ranging from <1 MoS4 > (highest oxidized state) to >5 MoS4 > (lowest oxidized state). This study emphasizes the excellent charge‐storage performances of Na2 MoS4 for Li‐ or Na‐ion batteries, and enriches the emerging library and knowledge of sulfide phases with mixed anionic and cationic redox properties. Abstract : A mixed ion–electron conducting amorphous phase of tetrathiamolybdate (MoS4 2− ) with mixed Mo and S valences, shows a sustainable reversible capacity of 500 mAh g −1 (black plot) derived from cumulative anionic sulfide (red plot) and cationic molybdenum (blue plot) redox properties. The material is equally suitable for lithium‐ and sodium‐cation storage, with further avenues to be explored toward multivalent and higher voltage redox materials.